The Women's International Democratic Federation, the Global South and the Cold War : defending the rights of women of the 'whole world'? - Gradskova, I︠U︡lii︠a︡ (Routledge, 2021)
"Yulia Gradskova is Associate Professor in History and works at the Department of History, Stockholm University, Sweden. Her research interests include Soviet and post-Soviet social and gender history, decolonial perspective on Soviet politics on emancipation of "woman of the East" and gender equality. Gradskova is the author of Soviet Politics of Emancipation of Ethnic Minority Women. Natsionalka (Springer, 2018) and co-editor of several books, including Gendering Postsocialism. Old Legacies and New Hierarchies (Routledge 2018, with Ildiko Asztalos Morell); Gender Equality on a Grand Tour. Politics and Institutions - the Nordic Council, Sweden, Lithuania and Russia (Brill, 2017 - with E. Blomberg, Y. Waldemarson and A. Zvinkliene)"--